2012
DOI: 10.1007/s11104-012-1183-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Populus tremula to heterogeneous B distributions in soil

Abstract: Background Poplars accumulate inordinate amounts of B in their leaves and are candidate plants for the remediation of B contaminated soil. We aimed to determine the effect of heterogeneous B distribution in soil by comparing the growth and B accumulation of young Populus tremula trees growing in soil with heterogeneous and homogeneous B distributions. Methods The first of two experiments focused on the tolerance and B accumulation of P. tremula under heterogeneous soil B distributions, while the second was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Some authors argued that the heterogenous pattern caused more photosynthetic products to be partitioned to underground organs, which lowered the growth of above-ground organs. However, another study on poplar stocks revealed that shoot growth was increased or unchanged in the heterogeneous pattern relative to the homogeneous pattern of Boron supply [ 50 ]. This was caused by the tradeoff between adjusting Boron deficiency and toxicity by signals within whole-plant cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argued that the heterogenous pattern caused more photosynthetic products to be partitioned to underground organs, which lowered the growth of above-ground organs. However, another study on poplar stocks revealed that shoot growth was increased or unchanged in the heterogeneous pattern relative to the homogeneous pattern of Boron supply [ 50 ]. This was caused by the tradeoff between adjusting Boron deficiency and toxicity by signals within whole-plant cycling.…”
Section: Discussionmentioning
confidence: 99%
“…The field of view for the neutron beam was 185*185 mm with an image resolution of about 200 μm. To cover the whole sample (with size of 250 * 300 mm), four individual radiographs with slight overlaps were taken and then stitched together, similar to Rees et al (2012) by ImageJ plugin 'Mosaic' (http://mosaic.mpi-cbg.de/?q=downloads/imageJ).…”
Section: Water Treatment Of Samplesmentioning
confidence: 99%
“…Not only trace elements but also other soil factors influencing root traits and morphology, such as water, air or macronutrients, often show quite heterogeneous distribution patterns (Hodge, 2010). Under well-defined conditions, poplar root growth was shown to be inhibited in soil patches with B concentrations >20 mg kg -1 (Rees et al, 2012), but there are no studies on the response of poplar roots to a spatially heterogeneous distribution of soil B under field conditions.…”
Section: Introductionmentioning
confidence: 99%